The impact of genetic variants of the IGF-1 axis on surgical outcomes and prognosis in ovarian cancer - Inês de Almeida Lopes; Mariana Moreira Pires; Deolinda Pereira; Valéria Tavares; Inês Guerra de Melo; Rui Medeiros (Molecular Biology Reports, 2026)
Background Ovarian cancer (OC) remains the most lethal gynaecological malignancy, largely due to late-stage diagnosis, tumour heterogeneity, and high recurrence rates. The insulin-like growth factor-1 (IGF-1) axis has been implicated in tumour proliferation, survival, and treatment resistance. Yet, the prognostic relevance of its genetic variants in OC is not well established. The present study aims to evaluate the impact of two IGF-1-related single-nucleotide polymorphisms (SNPs), IGF1 rs6220 and IGF1R rs2016347, on the clinical outcome of 330 OC patients. Methods and results SNP genotyping was performed using the TaqMan ® Allelic Discrimination methodology. Regarding IGF1 rs6220, G allele carriers presented significantly improved overall survival compared with AA homozygotes within the subgroup of women undergoing suboptimal cytoreductive surgery (residual disease ≥ 1 cm) ( p = 0.039). As for IGF1R rs2016347, the TT genotype was associated with shorter disease-free survival than A allele carriers within the well-differentiated tumour group ( p = 0.028). Conclusions These results indicate a context-dependent impact of IGF-1 axis polymorphisms on OC prognosis, suggesting their potential utility as molecular markers. Further validation in larger, independent cohorts, together with functional studies, is warranted to confirm these results and clarify the biological mechanisms underlying the influence of IGF-1-related genetic variants on OC behaviour.

Blue carbon inventories of Spain and Portugal for their inclusion in national climate mitigation strategies - Nerea Piñeiro-Juncal; Oscar Serrano; Carmen B. de los Santos; Nuria Marbà; Elena Díaz-Almela; Fernando Tuya; Inés Mazarrasa; Joxe Mikel Garmendia; Xosé Lois Otero; Karina Inostroza; Jordi F. Pagès; Gonzalo Mendez-Martínez; et al. (Marine Pollution Bulletin, 2026)

Estimation of the three coastal blue carbon pools in Avicennia germinans and Rhizophora racemosa within the Cacheu River Mangroves Natural Park (PNTC), Guinea-Bissau - Xu Wang; Namir Domingos Raimundo Lopes; Tianxin Li; Nametso Matomela; Rui Moutinho Sá (Ocean & Coastal Management, 2026)

Reassessing and Updating Regulatory Standards on the Declaration of Storage Conditions in the Product Information of Medicinal Products: An Evidence-Based Proposal under EMA Guidance - Helena Pericão; Henrique Cavaco; Miguel Dias; Luís Sarmento; Mário Magalhães; Bernardo Filipe; Herivelto Vieira; João Rita; Pedro Gonçalves; Matilde Vaz; Beatriz Coimbra; Beatriz Monteiro; et al. (Pharmaceutical Research, 2026)
Purpose The European Medicines Agency (EMA) guideline Declaration of Storage Conditions in the Product Information of Medicinal Products (CPMP/QWP/609/96/Rev.2) was last revised in 2007. Since then, advances in stability science, increased climatic variability, and evolving regulatory expectations have highlighted limitations in the framework, particularly the use of vague descriptors such as “room temperature” or “no special storage conditions.” This work reassesses the scientific and regulatory basis for storage statements, integrating current understanding of mean kinetic temperature (MKT), climate-related risks, and developments in ICH and WHO guidance, and proposes a harmonized revision (Rev.3). Methods A structured analysis of regulatory and scientific principles was conducted, incorporating MKT, climate-related risks, and developments in ICH and WHO guidance. These elements informed a revised framework and model storage statements, including a decision table linking stability outcomes to label statements. Results The proposed update introduces explicit temperature-based statements, strengthens the linkage between stability data and label wording, clarifies requirements for moisture- and light-sensitive products, expands guidance for sterile and reconstituted preparations, and provides contingency instructions for temperature excursions. A decision table mapping stability outcomes to label statements is included to support regulatory implementation. Conclusion This revision provides an updated synthesis of EMA, ICH, and WHO requirements, translating regulatory principles into clear storage statements and contingency guidance. It offers a more precise framework reducing ambiguity, supports justification of storage conditions through stability data and MKT-informed risk assessment, aiming to improve understanding among patients and healthcare professionals, strengthening real-world product quality and contributing to future EMA guideline development. Highlights Identifies scientific and regulatory limitations in current “no special storage conditions” terminology; Links ICH stability guidelines and climatic variability to precise storage statements; Proposes harmonised core label phrases for room temperature, fridge, and freezer; Introduces contingency labelling for climate-related and cold-chain excursions.

Coarse particulate matter air pollution in Porto Metropolitan area, Portugal: time series analysis, trends and implications for public policies - Simone Georges El Khouri Miraglia; Ronan Adler Tavella; Daniela Debone; Rui Moreira Barbosa; Flavio Manoel Rodrigues da Silva Júnior; Clara Lopes Ribeiro; Simone Morais; Marisa Alexandra Marques Freitas (Environmental Science and Pollution Research, 2026)
Air pollution remains a persistent environmental and public health concern in urban regions. This study presents a 22-year analysis (2001–2022) of coarse particulate matter (PM 10 ) concentrations across 15 monitoring stations in the Porto Metropolitan Area (PMA), Portugal. The stations, pre-classified by national authorities as traffic, background-urban, background-suburban, or industrial, were used to assess long-term temporal trends and spatial variability. Annual mean PM 10 concentrations were calculated and linear regression was applied to evaluate trends. Differences between station types were tested using statistical analysis. The results revealed consistent decline in PM 10 levels from the early 2000s to the mid-2010s, followed by stagnation or increases at several stations in the final years of the series. While higher concentrations were historically observed at traffic and industrial sites, no statistically significant differences in annual mean PM 10 concentrations were found between stations of different classifications or within classifications, even when comparing distinct time periods. This homogeneity suggests widespread regional exposure, likely driven by shared emission sources, atmospheric transport, and urban development patterns across the PMA. When compared to World Health Organization (WHO) air quality guidelines, exceedances were frequent and persistent. From 2001 to 2011, nearly all stations with valid data exceeded the 2005 guideline of 20 µg/m 3 . Between 2012 and 2020, the exceedances gradually decreased, although several stations still surpassed the guideline. However, under the 2021 WHO guideline (15 µg/m 3 ), all stations with valid data for 2021 and 2022 again exceeded the guideline. These findings highlight the need for integrated, long-term air quality policies. Clinical trial number: Not applicable.

Are all nanoplastics equally neurotoxic? Influence of size and surface functionalization on the toxicity of polystyrene nanoplastics in human neuronal cells - Carolina Mota; Ana Margarida Araújo; Maria Enea; Eulália Pereira; Ana Reis-Mendes; Rui Fernandes; Sofia Pacheco; Marlene Lúcio; Carla Martins Lopes; Isabel M.P.L.V.O. Ferreira; Márcia Carvalho (Environmental Pollution, 2026)

Surface-functionalized g-C3N4/3D-printed alkali-activated materials for the removal of emerging water pollutants - J.G. Cuadra; Nuno P.F. Gonçalves; K. Ben Tayeb; Catia Venâncio; S. Costa; I. Lopes; T. Trindade; J.A. Labrincha; Rui M. Novais (Chemical Engineering Journal, 2026)

Low oxidative stress of cephalopod early life stages under chronic and intermittent hypoxia - Mélanie Court; Marta Macau; Tânia Marquês; Tiago Repolho; Mário Diniz; Vanessa Madeira Lopes; Rui Rosa; José Ricardo Paula (Marine Biology, 2026)

Seamounts of Cabo Verde: A review of their ecological and economic significance, anthropogenic impacts, and conservation needs - Covadonga Orejas; Beatriz Vinha; Gillian B. Ainsworth; Sarah Saldanha; Teresa Militão; Christian Mohn; Thor H. Hansteen; Sara S. Ratão; Henk-Jan Hoving; Teresa Amaro; Dominique M.J. Anderson; Deusa Araújo; et al. (Progress in Oceanography, 2026)

A summary of the Lucy Ashton resistance prediction workshop - Rui Lopes; Arash Eslamdoost; Rickard E. Bensow; Dmitriy Ponkratov; Anja Kömpe; Paolo Geremia; Çagan Birant Pekküçük; Cagri Aydin; Diego Villa; Dimitris Ntouras; Dong Cheol Seo; Gennaro Rosano; et al. (Ocean Engineering, 2026)

Benchmark Reynolds-averaged Navier-Stokes study of a generic marine rudder’s static stall characteristics - Mark Bettle; Luc Bordier; Myriam Slama; Emmanuel François; Serge Toxopeus; Craig Marshall; Richard Pattenden; Riccardo Broglia; Shawn Aram; Abel Vargas; Rui Lopes; Magnus Vartdal; et al. (Ocean Engineering, 2025)

Leveraging local environmental management in the scope of an administrative decentralization process: The case of Portuguese coastal municipalities - Lina Ortiz Arroyave; Rita Lopes; Rui Santos (Journal of Environmental Management, 2025)

Impact of Building-Grid interaction signals on energy flexibility at cluster Level: Insights from two case studies - Tuğçin Kırant-Mitić; Monika Hall; George Dawes; Rui Amaral Lopes (Energy and Buildings, 2025)

Energy flexibility at multi-building scales: A review of the dominant factors and their uncertainties - George Dawes; Tuğçin Kirant-Mitić; Zixin Jiang; Jérôme Le Dréau; Hanmin Cai; Jiyuan Cui; Jordan Townsend; Adamantios Bampoulas; Rongling Li; Rui Amaral Lopes; Bing Dong (Energy and Buildings, 2025)

Modeling the impact of electric vehicle charging on Lisbon's electricity distribution network - Miguel Mouquinho Cardinha; Rui Amaral Lopes; Nuno Amaro (Utilities Policy, 2025)

A comprehensive review of synthetic image generation methods in remote sensing - Julio Castro Lopes; Jose Luis Oliveira; Rui Pedro Lopes (International Journal of Remote Sensing, 2025)

Assessing the impact of agrifood byproduct-based bioplastics on soil microbial communities and functioning - Marija Prodana; Catarina Malheiro; Joana Lopes; Sara Peixoto; Rui G. Morgado; Idalina Gonçalves; Paula Ferreira; Manuel A. Coimbra; Artur Alves; Micael F.M. Gonçalves; Sandra Hilário; Susana Loureiro (International Biodeterioration & Biodegradation, 2025)

A population under smoke: fire events trigger severe air pollution in Portugal - Simone Georges El Khouri Miraglia; Daniela Debone; Clara Lopes Ribeiro; Rui Moreira Barbosa; Ronan Adler Tavella; Flavio Manoel Rodrigues da Silva-Júnior; Manuela Vieira da Silva; Marisa Alexandra Marques Freitas (Environmental Science and Pollution Research, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Resistance prediction using CFD at model- and full-scale and comparison with measurements - Rui Lopes; Arash Eslamdoost; Rikard Johansson; Seemontini RoyChoudhury; Rickard E. Bensow; Per Hogström; Dmitriy Ponkratov (Ocean Engineering, 2025)

Chemical characterization and antioxidant potential of Arthrospira sp., Thalassiosira sp., and Raphidonema sp. - Vera Castro; Ana Teixeira; Luara Simões; Franklin Chamorro; Catarina Lourenço-Lopes; Celina Parreira; Sara M. Badenes; Luís Costa; Miguel A. Prieto; Rui Oliveira; Alberto C.P. Dias (Food Chemistry, 2025)

Predicted environmental concentration (PEC), environmental risk assessment (ERA) and prioritization of antiretroviral drugs (ARVs) in seawater from Guarujá (Brazilian coastal zone) - Leonardo Teixeira Ramos; Vinicius Roveri; Walber Toma; Rafael Barreiros Kiyotani; Wellington Rui Andrade de Assis Junior; Ana Paula Metropolo; Gilmar Aparecido dos Santos; Aírton Zogaib Rodrigues; Luciana Lopes Guimarães (Marine Environmental Research, 2025)

Seasonal monitoring, ecological risk assessment, and prioritization of pharmaceuticals in a tropical semi-enclosed bay (Santos, São Paulo coast, Brazil) - Vinicius Roveri; Luciana Lopes Guimarães; Rafael Barreiros Kiyotani; Wellington Rui Andrade de Assis Junior; Ana Paula Metropolo; Gilmar Aparecido dos Santos; Aírton Zogaib Rodrigues; Camilo Dias Seabra Pereira; Alberto Teodorico Correia (Marine Environmental Research, 2025)

Addressing the urgent climate and biodiversity crisis through strategic ecosystem restoration in Brazil - Luisa Fernanda Liévano-Latorre; Juliana M. de Almeida-Rocha; Alberto Akama; Hernani Alves Almeida; Ricardo Teixeira Gregório Andrade; Marcelo Rodrigues dos Anjos; Yasmine Antonini; Thaise de Oliveira Bahia; Flavia Rodrigues Barbosa; Reinaldo Imbrozio Barbosa; Claudia Franca Barros; Helena Godoy Bergallo; et al. (Biological Conservation, 2025)

Long-term impacts of salinity and temperature changes on Brachionus calyciflorus populations: understanding the role of intraspecific variability - Lishani Wijewardene; Cátia Venâncio; Rui Ribeiro; Isabel Lopes (Environmental Science and Pollution Research, 2025)
Worldwide, many coastal freshwater ecosystems suffer from seawater intrusion. In addition to this stressor, it is likely that the biota inhabiting these ecosystems will also need to deal with climate change-related temperature fluctuations. The resilience of populations to long-term exposure to these stressors will depend on their genetic diversity, a key for their adaptation to changing environments. Accordingly, this study aimed to understand the long-term effects of salinity and temperature on the population density dynamics of the rotifer Brachionus calyciflorus by considering intra-specific variability. Six clonal lineages of B. calyciflorus , exhibiting differential lethal sensitivity (LC 50,24 h ) to salinity, were exposed for at least 34 days, to a control and to artificial seawater (at a conductivity corresponding to the LC 70,24 h for the most tolerant clonal lineage = 9.89 mS/cm), under three temperatures: 17, 20 (standard) and 23 °C. Long-term exposure to artificial seawater affected population densities, leading to the extirpation of some salinity-tolerant clonal lineages earlier than that of salinity-sensitive lineages. This inversion in short- and long-term sensitivity may suggest a higher susceptibility of populations when exposed to long periods of increased salinity. The negative effects caused by artificial seawater were enhanced at 17 °C and 23 °C, with an even earlier occurrence of extirpation of some clonal lineages, namely, two clonal lineages considered tolerant to artificial seawater. The results suggest the potential synergistic effects of the two abiotic stressors when combined. Overall, a lack of association between the clonal lineages’ short- and long-term sensitivity to salinity or their sensitivity to salinity under different temperature scenarios was observed. These results suggest an increased risk to the resilience of B. calyciflorus populations exposed to climate change-related scenarios of increased salinity and temperature fluctuations owing to an enhanced reduction in their genetic variability.

Consistent cell‐specific carbon fixation rates by small eukaryotic phytoplankton in contrasting nutrient‐limited conditions - Denise Rui Ying Ong; Andrés Gutiérrez‐Rodríguez; Karl A. Safi; Dominique Marie; Karen E. Selph; Michael R. Stukel; Moira Décima; Adriana Lopes dos Santos (Limnology and Oceanography, 2025)
Small phytoplankton, consisting of pico and nano size fractions, are diverse in size and taxonomy. Yet, the differences in their productivity and taxonomic diversity are poorly described. Here, we measured the cell‐specific carbon fixation rates of picocyanobacteria Synechococcus , picoeukaryote, and nanoeukaryote populations, while unveiling their taxonomic composition in oligotrophic subtropical and high‐nutrient low‐chlorophyll subantarctic waters. We coupled 24 h in situ radiolabeled 14 C incubations to flow cytometry sorting and DNA metabarcoding from the same incubated samples, offering a direct account of the community associated with the carbon fixation rates measured. In both water masses, nanoeukaryotes had the highest cell‐specific carbon fixation rate, followed by picoeukaryotes and Synechococcus (2.24 ± 29.99, 2.18 ± 2.08, and 0.78 ± 0.55 fgC cell −1 h −1 , respectively). The cell‐specific carbon fixation rates and growth rates of Synechococcus were threefold higher in subtropical compared to subantarctic waters, while the rates of picoeukaryotes and nanoeukaryotes had no significant difference between the biogeochemically‐contrasting water masses. Sorted picoeukaryote populations were dominated by Mamiellophyceae, Pelagophyceae, Prymnesiophyceae, and Chrysophyceae, while nanoeukaryote populations were dominated by Dinophyceae and Prymnesiophyceae. Despite significant differences in their taxonomic composition, the sorted picoeukaryote populations in subantarctic waters and nanoeukaryote populations in subtropical and subantarctic waters were dominated by taxa reported in the literature as able to engage in phago‐mixotrophic strategies (Prymnesiophyceae, Chrysophyceae, and Dinophyceae), suggesting that such trophic strategy might be applied by discrete small photosynthetic eukaryote populations to alleviate macronutrient and iron stress.

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

Temporal variability and ecological risks of pharmaceuticals and cocaine during the Christmas and New Year holidays in a beach area of North Coast of São Paulo, Brazil - Vinicius Roveri; Luciana Lopes Guimarães; Rafael Barreiros Kiyotani; Wellington Rui Andrade de Assis Junior; Ana Paula Metropolo; Gilmar Aparecido dos Santos; Aírton Zogaib Rodrigues; Camilo Dias Seabra Pereira; Alberto Teodorico Correia (Marine Environmental Research, 2024)

A numerical study on the influence of crossflow transition on a marine propeller in open water - Rui Lopes; Arash Eslamdoost; Rikard Johansson; Seemontini RoyChoudhury; Rickard E. Bensow (Ocean Engineering, 2024)

Use of crude glycerin in dairy goat feeding and its effects on milk and cheese performance and quality - Rodrigo Barbosa de Andrade; Kelly Cristina dos Santos; Érica Carla Lopes da Silva; Edneide Rodrigues da Silva; Michel do Vale Maciel; João Paulo Ismério dos Santos Monnerat; Dorgival Morais de Lima Júnior; Neila Mello dos Santos Cortez; Maria Gabriela da Conceição; Susana Paula Almeida Alves; Rui José Branquinho de Bessa; Francisco Fernando Ramos de Carvalho (Animal Feed Science and Technology, 2024)

Cork oak woodlands and decline: a social-ecological review and future transdisciplinary approaches - Margarida Lopes-Fernandes; Ernesto Martínez-Fernández; Rui Alves; Daniel Boa-Nova; Cristina Branquinho; Miguel N Bugalho; Felipe Campos-Mardones; Agustin Coca-Pérez; Amélia Frazão-Moreira; Marco Marques; Javier Moreno-Ortiz; Octávio Paulo; et al. (Agroforestry Systems, 2024)
Cork oak woodlands are socio-ecosystems recognized as biodiversity hotspots, a fundamental economic source for companies and local communities as well as an identitarian landscape for residents and visitors. Cork oak woodlands, however, are facing tree mortality and lack of regeneration. Considering the oak decline scenario, we present Iberian cork oak montado/dehesa as a socio-ecosystem facing climate change, management transformations, local knowledge crisis and social uncertainty. We review montado s/ dehesa s research through time and by different scholar perspectives. We defend that from an interdisciplinary and transdisciplinary perspective, including the experience and evidence observed in terrain, debate should be stimulated, and novel conceptual approaches may contribute to finding solutions. We argue that the confluence of ecology, genetics, anthropology and local knowledge can be explored to unveil the complexities and the challenges of these socio-ecosystems and contribute to prevent and mitigate threats to it. We propose a methodological approach built together with scientists, managers and workers, that can explore oak translocations, socio-ecological interactions models, knowledge transfer and other ways to overcome Iberian cork oak woodlands socio-environmental crisis.

Sleep Quality of Heavy Vehicles’ Professional Drivers: An Analysis Based on Self-Perceived Feedback - Brigida Monica Faria; Tatiana Lopes; Alexandra Oliveira; Rui Pimenta; Joaquim Gonçalves; Victor Carvalho; Marta Gonçalves; Luis Paulo Reis (Sleep and Vigilance, 2024)
Introduction Sleep is a crucial biological need for all individuals, being reparative on a physical and mental level. Driving heavy vehicles is a task that requires constant attention and vigilance, and sleep deprivation leads to behavioral and physiological changes that can develop sleep disorders which can put lives at risk. Objectives The main objectives of this study are to describe and evaluate sleep quality, excessive daytime sleepiness, circadian preference, and risk of suffering from obstructive sleep apnea in a population of Portuguese professional drivers. Methods To fulfill the objectives, 43 Portuguese professional drivers, between 23 and 63 years old, answered validated questionnaires: Epworth Sleepiness Scale, Morningness–Eveningness, Stop-Bang Questionnaire, and Pittsburgh Sleep Quality Index. Results Results indicated that older drivers tend to experience higher daytime sleepiness (11 ± 3.4; p = 0.002) and obstructive sleep apnea risk (4.5 ± 1.5; p = 0.03). Regarding sleep quality, the majority of drivers were classified with poor sleep quality (74.4%). It was possible to infer statistical differences between groups based on body mass index ( p = 0.037), the type of route ( p = 0.01), and physical activity ( p = 0.005). Conclusion Drivers have an indifferent circadian preference and small-course drivers have a worse sleep health perception. Therefore, it is essential to implement prevention programs, promoting the basic rules for better sleep quality as well as identifying sleep disorders to minimize possible road accidents.

Horizontal migration of zooplankton in lake–wetland interfaces. Can temperature-driven surface exchange flows modulate its patterns? - Joana Luísa Pereira; Ana Sofia Lopes; Júlia Silva; Tânia Vidal; Nelson Abrantes; Daniela Santos; Moisés Brito; Rui M. L. Ferreira; Fernando J. M. Gonçalves; Ana Margarida Ricardo (Aquatic Sciences, 2024)
Lake ecology can be affected by exchange flows driven by horizontal temperature gradients in lake–wetland interfaces. In this work, we investigate the hypothesis that thermally driven flows modulate the horizontal migration patterns of freshwater zooplankters. A 48-h field campaign in a shallow lake (Lake Vela, Quiaios, Portugal) was carried out to test this hypothesis. Thermal differences between the littoral and limnetic areas were measured along two transects featuring a Schoenoplectus lacustris and a Myriophyllum aquaticum stand in the littoral. In parallel, the physiochemistry and chlorophyll a, as a proxy for food availability differences between the littoral and the limnetic zones, were monitored. Zooplankton samples were collected for assessing overall and group-specific number-density differences. The diel period (day or night) and the site (littoral or limnetic zone) did not interact significantly to modulate the variation patterns for the studied physiochemical variables, indicating that these parameters should not explain horizontal zooplankton distribution patterns. The expected patterns for zooplankton diel horizontal migration as driven by the presence of visual predators were occasionally confirmed by our limnetic versus littoral abundance records through time, depending on the transect. Group-specific abundance patterns indicate particular features: copepods always preferred the littoral over the limnetic zone regardless of the diel period; chydorids always preferred the littoral zone regardless of the macrophyte stand involved; bosminids tended to preferentially concentrate in the limnetic zone. No consistent relationship was identified between the expected flow direction due to temperature differences and zooplankton abundance changes, although it occasionally occurred through the dataset.

Botulinum Toxin in Peripherally-Induced Movement Disorders – A Multidisciplinary Approach - Rui Peresa; Ana Sofia Lopes; Cristina Costa (Toxicon, 2024)

Octopus crawling on land: physiological and biochemical responses of Octopus vulgaris to emersion - Janina Leonie Röckner; Vanessa M. Lopes; José Ricardo Paula; Maria Rita Pegado; Martim Costa Seco; Mário Diniz; Tiago Repolho; Rui Rosa (Marine Biology, 2024)

Impacts of acute hypoxia on the short-snouted seahorse metabolism and behaviour - Matilde Gomes; Vanessa M. Lopes; Monica G. Mai; José R. Paula; Regina Bispo; Hugo Batista; Catarina Barraca; Núria Baylina; Rui Rosa; Marta S. Pimentel (Science of The Total Environment, 2023)

Effects of diets differing in the concentrate-to-roughage ratio on meat quality and fatty acids composition in abomasal digesta and meat from thin-tail and fat-tail Brazilian ovine breeds - Luana França dos Anjos; Rui José Branquinho de Bessa; Henrique Nunes Parente; Susana Paula Alves; Aline Vieira Landim; Anderson de Moura Zanine; Anderson Lopes Pereira; Graziele Silva de Oliveira; Daniele de Jesus Ferreira; Alexandre Fernandes Perazzo; Mayara Raposo dos Santos; Michelle de Oliveira Maia Parente (Small Ruminant Research, 2023)

Developing energy flexibility in clusters of buildings: A critical analysis of barriers from planning to operation - Jérôme Le Dréau; Rui Amaral Lopes; Sarah O'Connell; Donal Finn; Maomao Hu; Humberto Queiroz; Dani Alexander; Andrew Satchwell; Doris Österreicher; Ben Polly; Alessia Arteconi; Flavia de Andrade Pereira; et al. (Energy and Buildings, 2023)

Pre-exposure to seawater or chloride salts influences the avoidance-selection behavior of zebrafish larvae in a conductivity gradient - Cátia Venâncio; Rui Ribeiro; Isabel Lopes (Environmental Pollution, 2023)

Effect of cactus species in the diets of dairy goats on feed efficiency, milk yield, and milk and cheese composition - Thalita Polyana Monteiro Araújo; Dorgival Morais de Lima Júnior; Érica Carla Lopes da Silva; Maria Luciana Menezes Wanderley Neves; Kelly Cristina dos Santos; Marcelo de Andrade Ferreira; João Paulo Ismério Monnerat; Susana Paula Almeida Alves; Rui José Branquinho de Bessa; Francisco Fernando Ramos de Carvalho (Animal Feed Science and Technology, 2023)

Combined effects of two abiotic stressors (salinity and temperature) on a laboratory-simulated population of Daphnia longispina - Cátia Venâncio; Lishani Wijewardene; Rui Ribeiro; Isabel Lopes (Hydrobiologia, 2023)
Sea level rise is expected to continue apace, with a concomitant rise in temperature on the globe's surface. Natural populations genetic pool compromised by increased salinity would contribute to decrease resilience under future temperature changes. Therefore, this work aimed to understand the long-term effects of salinization on the genetic diversity of a cladoceran-simulated laboratory population under different temperature regimes. For that, six clonal lineages of the cladoceran Daphnia longispina were chosen based on their reported differential lethal sensitivity (LC x ) to salinity. The chronic experiment was initiated when each individual clonal lineage reached the population’s carrying capacity, and then were exposed to the LC 70,48 h for the most tolerant clonal lineage of D. longispina (corresponding to 5.91 mS/cm) to 17°C, 20°C and 23°C for at least 30 days. Salinity affected D. longispina survival and reproduction, with the disappearance of salt-tolerant earlier than salt-sensitive lineages after chronic exposures. Different sensitivity ranks were observed for clonal lineages when comparing short-term and chronic survival, most probably due to acclimation-driven population recovery. Non-optimal tested temperatures (17°C and 23°C) enhanced negative effects of salinity through loss of the most sensitive clonal lineages, suggesting a potential future synergistic effect between both abiotic factors.

Predicting future coastal land use/cover change and associated sea-level impact on habitat quality in the Northwestern Coastline of Guinea-Bissau - Namir Domingos Raimundo Lopes; Tianxin Li; Peng Zhang; Nametso Matomela; Harrison Odion Ikhumhen; Rui M. Sá (Journal of Environmental Management, 2023)

Effects of tidal emersion and marine heatwaves on cuttlefish early ontogeny - João Coelho; Mélanie Court; Eve Otjacques; Vanessa M. Lopes; José Ricardo Paula; Tiago Repolho; Mário Diniz; Rui Rosa (Marine Biology, 2023)

Coastal vulnerability assessment based on multi-hazards and bio-geophysical parameters. case study - northwestern coastline of Guinea-Bissau - Namir Domingos Raimundo Lopes; Tianxin Li; Nametso Matomela; Rui Moutinho Sá (Natural Hazards, 2022)

Differential Effects of Food Restriction and Warming in the Two-Spotted Goby: Impaired Reproductive Performance and Stressed Offspring - Ana F. Lopes; Robyn Murdoch; Sara Martins-Cardoso; Carolina Madeira; Pedro M. Costa; Ana S. Félix; Rui F. Oliveira; Narcisa M. Bandarra; Catarina Vinagre; Ana R. Lopes; Emanuel J. Gonçalves; Ana Margarida Faria (Fishes, 2022)
Climate change is a growing threat to marine organisms and ecosystems, and it is already modifying ocean properties by, for example, increasing temperature and decreasing pH. Increasing water temperature may also lead to an impairment of primary productivity and an overall depletion of available zooplankton. Understanding how the crossover between warming and zooplankton availability impacts fish populations has paramount implications for conservation and mitigation strategies. Through a cross factorial design to test the effects of ocean temperature and food availability in a temperate marine teleost, Pomatochistus flavescens, we showed that hindered feeding impacted sheltering and avoidance behaviour. Also, low food availability impaired fish reproduction, particularly male reproduction, as the expression of cyp11b1, a gene with a pivotal role in the synthesis of the most important fish androgen, 11-ketotestosterone, was significantly reduced under a low food regime. In contrast, temperature alone did not affect reproductive success, but offspring showed increased saturated fatty acid content (embryos) and increased lipid peroxidation (larvae). Altogether, food availability had a stronger effect on fitness, showing that coping with elevated temperatures, an ability that may be expected in shallow-water fish, can be indirectly impacted, or even overwhelmed, by the effects of ocean warming on primary productivity and downstream ecological processes.

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Strong and lasting impacts of past global warming on baleen whales and their prey - Andrea A. Cabrera; Elena Schall; Martine Bérubé; Pia Anderwald; Lutz Bachmann; Simon Berrow; Peter B. Best; Phillip J. Clapham; Haydée A. Cunha; Luciano Dalla Rosa; Carolina Dias; Kenneth P. Findlay; et al. (Global Change Biology, 2022)
Global warming is affecting the population dynamics and trophic interactions across a wide range of ecosystems and habitats. Translating these real‐time effects into their long‐term consequences remains a challenge. The rapid and extreme warming period that occurred after the Last Glacial Maximum (LGM) during the Pleistocene–Holocene transition (7–12 thousand years ago) provides an opportunity to gain insights into the long‐term responses of natural populations to periods with global warming. The effects of this post‐LGM warming period have been assessed in many terrestrial taxa, whereas insights into the impacts of rapid global warming on marine taxa remain limited, especially for megafauna. In order to understand how large‐scale climate fluctuations during the post‐LGM affected baleen whales and their prey, we conducted an extensive, large‐scale analysis of the long‐term effects of the post‐LGM warming on abundance and inter‐ocean connectivity in eight baleen whale and seven prey (fish and invertebrates) species across the Southern and the North Atlantic Ocean; two ocean basins that differ in key oceanographic features. The analysis was based upon 7032 mitochondrial DNA sequences as well as genome‐wide DNA sequence variation in 100 individuals. The estimated temporal changes in genetic diversity during the last 30,000 years indicated that most baleen whale populations underwent post‐LGM expansions in both ocean basins. The increase in baleen whale abundance during the Holocene was associated with simultaneous changes in their prey and climate. Highly correlated, synchronized and exponential increases in abundance in both baleen whales and their prey in the Southern Ocean were indicative of a dramatic increase in ocean productivity. In contrast, the demographic fluctuations observed in baleen whales and their prey in the North Atlantic Ocean were subtle, varying across taxa and time. Perhaps most important was the observation that the ocean‐wide expansions and decreases in abundance that were initiated by the post‐LGM global warming, continued for millennia after global temperatures stabilized, reflecting persistent, long‐lasting impacts of global warming on marine fauna.

Modelling the impact of nucleolin expression level on the activity of F3 peptide-targeted pH-sensitive pegylated liposomes containing doxorubicin - Rui Lopes; Kevin Shi; Nuno A. Fonseca; Adelina Gama; José S. Ramalho; Luís Almeida; Vera Moura; Sérgio Simões; Bruce Tidor; João N. Moreira (Drug Delivery and Translational Research, 2022)

ATLANTIC POLLINATION: a data set of flowers and interaction with nectar‐feeding vertebrates from the Atlantic Forest - Joice Iamara‐Nogueira; Natália Targhetta; Gina Allain; Adriano Gambarini; Alessandra R. Pinto; Ana Maria Rui; Andréa C. Araújo; Ariadna Lopes; Brenda Pereira‐Silva; Bruna Bertagni de Camargo; Caio Graco Machado; Caio Missagia; et al. (Ecology, 2022)
Flowering plant species and their nectar‐feeding vertebrates exemplify some of the most remarkable biotic interactions in the Neotropics. In the Brazilian Atlantic Forest, several species of birds (especially hummingbirds), bats, and non‐flying mammals, as well as one lizard feed on nectar, often act as pollinators and contribute to seed output of flowering plants. We present a dataset containing information on flowering plants visited by nectar‐feeding vertebrates and sampled at 166 localities in the Brazilian Atlantic Forest. This dataset provides information on 1902 unique interactions among 515 species of flowering plants and 129 species of potential vertebrate pollinators and the patterns of species diversity across latitudes. All plant–vertebrate interactions compiled were recorded through direct observations of visits, and no inferences of pollinators based on floral syndromes were included. We also provide information on the most common plant traits used to understand the interactions between flowers and nectar‐feeding vertebrates: plant growth form, corolla length, rate of nectar production per hour in bagged flowers, nectar concentration, flower color and shape, time of anthesis, presence or absence of perceptible fragrance by human, and flowering phenology as well as the plant’s threat status by International Union for Conservation of Nature (IUCN) classification. For the vertebrates, status of threat by IUCN classification, body mass, bill or rostrum size are provided. Information on the frequency of visits and pollen deposition on the vertebrate’s body is provided from the original source when available. The highest number of unique interactions is recorded for birds (1771) followed by bats (110). For plants, Bromeliaceae contains the highest number of unique interactions (606), followed by Fabaceae (242) and Gesneriaceae (104). It is evident that there was geographical bias of the studies throughout the southeast of the Brazilian Atlantic Forest and that most effort was directed to flower–hummingbird interactions. However, it reflects a worldwide tendency of more plants interacting with birds compared with other vertebrate species. The lack of similar protocols among studies to collect basic data limits the comparisons among areas and generalizations. Nevertheless, this dataset represents a notable effort to organize and highlight the importance of vertebrate pollinators in this hotspot of biodiversity on Earth and represents the data currently available. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or scientific events.

Identification and in silico characterization of structural and functional impacts of genetic variants in milk protein genes in the Zebu breeds Guzerat and Gyr - Carolina Guimarães Ramos Matosinho; Izinara Cruz Rosse; Pablo Augusto Souza Fonseca; Francislon Silva de Oliveira; Fausto Gonçalves dos Santos; Flávio Marcos Gomes Araújo; Anna Christina de Matos Salim; Beatriz Cordenonsi Lopes; Wagner Antonio Arbex; Marco Antônio Machado; Maria Gabriela Campolina Diniz Peixoto; Rui da Silva Verneque; et al. (Tropical Animal Health and Production, 2021)

Co-creating a Vision and Roadmap for Circular Economy in the Food and Beverages Packaging Sector - Rita Lopes; Rui Santos; Nuno Videira; Paula Antunes (Circular Economy and Sustainability, 2021)

Global phylogeography of sailfish: deep evolutionary lineages with implications for fisheries management - Bruno Lopes da Silva Ferrette; Bruno Mourato; Fábio Hissa Vieira Hazin; Freddy Arocha; Samuel Mackey Williams; Carlos Egberto Rodrigues Junior; Fábio Porto-Foresti; Alberto Ferreira de Amorim; Matheus Marcos Rotundo; Rui Coelho; John P. Hoolihan; Fambaye Ngom Sow; et al. (Hydrobiologia, 2021)

The role of TP53 pathogenic variants in early-onset HER2-positive breast cancer - Carla Escudeiro; Carla Pinto; Joana Vieira; Ana Peixoto; Pedro Pinto; Manuela Pinheiro; Catarina Santos; Joana Guerra; Susana Lisboa; Rui Santos; João Silva; Conceição Leal; et al. (Familial Cancer, 2021)

Designer Cathinones N-Ethylhexedrone and Buphedrone Show Different In Vitro Neurotoxicity and Mice Behaviour Impairment - Cristina de Mello-Sampayo; Ana Rita Vaz; Sara C. Henriques; Adelaide Fernandes; Fabiana Paradinha; Pedro Florindo; Paulo Faria; Rui Moreira; Dora Brites; Alvaro Lopes (Neurotoxicity Research, 2021)

Approaching Sea-Level Rise (SLR) Change: Strengthening Local Responses to Sea-Level Rise and Coping with Climate Change in Northern Mozambique - Serafino Afonso Rui Mucova; Ulisses Miranda Azeiteiro; Walter Leal Filho; Carina Lurdes Lopes; João Miguel Dias; Mário Jorge Pereira (Journal of Marine Science and Engineering, 2021)
Mean sea-level is expected to rise significantly by 2100 in all scenarios, including those compatible with the objectives of the Paris Climate Agreement. Global sea level rise projections indicate devastating implications for populations, ecosystem services and biodiversity. The implications of the sea-level rise (SLR) on low-lying islands and coastal regions and communities are substantial and require deep-rooted coping measures. In the absence of adequate responses for coping, Mozambique is expected to record huge losses, with an impact on the economy and development in many sectors of its coastal regions mainly in northern Mozambique. This research aimed to perform projections on SLR in Mozambique, and to understand its role and implications on the north coast of the country. SLR was estimated through the analysis of model outputs that support the global estimates of the fifth IPCC report near the Mozambican coast, for each of the four representative concentration pathways (RCPs) scenarios. Regional coastline retreat and coastal erosion were estimated through the results of global sandy coastlines projections developed by Vousdoukas. Mean sea-level rise projections indicate that regional estimates for the Mozambican coast are relative higher than global estimates (~0.05 m) for all representative concentration pathways (RCPs). Yet, we highlight significant differences in sea-level rises of 0.5 m, 0.7 m or 1.0 m by 2100 compared to the global mean. It is expected that with the increase in the mean sea level in the northern part of the Mozambican coast, erosive effects will increase, as well as the retreat of the coastline until 2100. With this, the tourism sector, settlements, ecosystem services and local populations are expected to be significantly affected by 2050, with increased threats in 2100 (RCP4.5, RCP8.5). Local responses for coping are proposed and properly discussed for the RCP4.5 and RCP8.5 scenarios through 2100.

Removal of bromate from drinking water using a heterogeneous photocatalytic mili-reactor: impact of the reactor material and water matrix - Gustavo S. Cunha; Sara G. S. Santos; Bianca M. Souza-Chaves; Tânia F.C.V. Silva; João Paulo Bassin; Márcia W.C. Dezotti; Rui A.R. Boaventura; Madalena M. Dias; José Carlos B. Lopes; Vítor J.P. Vilar (Environmental Science and Pollution Research, 2019)

Stenophagy as a Pathway for the Occurrence of Unique Coral Fatty Acid Biomarkers in Higher Branches of the Marine Tree of Life: The Nudibranch Armina maculata Case - Rui Rosa; Catarina Santos; Ana Lopes; Miguel Baptista; Eduardo Sampaio; Inês C. Rosa; Tiago Repolho (Ocean Science Journal, 2019)

Deep-sea seven-arm octopus hijacks jellyfish in shallow waters - Rui Rosa; Jesse T. Kelly; Vanessa M. Lopes; José R. Paula; João Gonçalves; Ricardo Calado; Mark D. Norman; João P. Barreiros (Marine Biodiversity, 2019)

Spatial distance and climate determine modularity in a cross‐biomes plant–hummingbird interaction network in Brazil - Andréa Cardoso Araujo; Ana M. Martín González; Brody Sandel; Pietro K. Maruyama; Erich Fischer; Jeferson Vizentin‐Bugoni; Francielle Paulina de Araújo; Aline Góes Coelho; Rogério Rodrigues Faria; Glauco Kohler; Flor Maria Guedes Las‐Casas; Ariadna Valentina Lopes; et al. (Journal of Biogeography, 2018)
Aim We examined the effects of space, climate, phylogeny and species traits on module composition in a cross‐biomes plant–hummingbird network. Location Brazil, except Amazonian region. Methods We compiled 31 local binary plant–hummingbird networks, combining them into one cross‐biomes metanetwork. We conducted a modularity analysis and tested the relationship between species’ module membership with traits, geographical location, climatic conditions and range sizes, employing random forest models. We fitted reduced models containing groups of related variables (climatic, spatial, phylogenetic, traits) and combinations of groups to partition the variance explained by these sets into unique and shared components. Results The Brazilian cross‐biomes network was composed of 479 plant and 42 hummingbird species, and showed significant modularity. The resulting six modules conformed well to vegetation domains. Only plant traits, not hummingbird traits, differed between modules, notably plants’ growth form, corolla length, flower shape and colour. Some modules included plant species with very restricted distributions, whereas others encompassed more widespread ones. Widespread hummingbirds were the most connected, both within and between modules, whereas widespread plants were the most connected between modules. Among traits, only nectar concentration had a weak effect on among‐module connectivity. Main conclusions Climate and spatial filters were the main determinants of module composition for hummingbirds and plants, potentially related to resource seasonality, especially for hummingbirds. Historical dispersal‐linked contingency, or environmental variations not accounted for by the explanatory factors here evaluated, could also contribute to the spatial component. Phylogeny and morphological traits had no unique effects on the assignment of species to modules. Widespread species showed higher within‐ and/or among‐module connectivity, indicating their key role connecting biomes, and, in the case of hummingbirds, communities within biomes. Our results indicate that biogeography and climate not only determine the variation of modularity in local plant–animal networks, as previously shown, but also affect the cross‐biomes network structure.

Tailoring structure and technological properties of plant proteins using high hydrostatic pressure - Rui P. Queirós; Jorge A. Saraiva; José A. Lopes da Silva (Critical Reviews in Food Science and Nutrition, 2018)

Biology and ecology of the world’s largest invertebrate, the colossal squid (Mesonychoteuthis hamiltoni): a short review - Rui Rosa; Vanessa M. Lopes; Miguel Guerreiro; Kathrin Bolstad; José C. Xavier (Polar Biology, 2017)

Phylogeography and phylogeny of the genus Acanthonyx (Decapoda, Epialtidae) in the north‐east Atlantic and Mediterranean - Ana I. Tavares; M. Pilar Cabezas; Raquel Xavier; Madalena Branco; Fernando P. Lima; Rui Seabra; Pedro A. Ribeiro; Evandro P. Lopes; António M. Santos (Zoologica Scripta, 2017)
The genus Acanthonyx Latreille, 1828 (Majoidea, Epialtidae) contains 17 or 18 known species, depending on competing taxonomic views, that are widely distributed across the world. Morphologically, most species look superficially alike, and therefore, similar taxonomic concepts have been described under different names. Consequently, there is today a considerable list of synonyms, which further complicates the taxonomy of the genus Acanthonyx . In this study, we conducted a phylogeographical and phylogenetic analysis of populations of the genus Acanthonyx in the NE Atlantic, Mediterranean and Macaronesia using the mitochondrial cytochrome oxidase subunit I ( COI ) and the nuclear 28S rRNA loci. Our phylogenetic and phylogeographical results revealed that Acanthonyx lunulatus sensu lato is a complex of three distinct lineages: one corresponding to the previously described Acanthonyx brevifrons , another to A. lunulatus sensu stricto and a third to a yet undescribed group. Whereas our results confirms that A. brevifrons deserves the status of a species, as it can be easily distinguishable from A. lunulatus by a few morphological traits, we could not find any such traits suitable for the discrimination between A. lunulatus sensu stricto and the third lineage. Furthermore, the degree of COI divergence between this lineage and A. lunulatus is below average levels for Decapoda species. Yet, no shared haplotypes have been detected between them. The differences found in the nuclear gene (indels), together with the sympatric occurrence of the two forms, prompt for a more detailed analysis of this group. Overall, the results show that significant genetic differentiation between specimens with similar morphology occurs in the Epialtidae, thus reinforcing the importance of combining morphological and genetic tools to fully resolve the taxonomy of these decapods.

Global patterns of interaction specialization in bird–flower networks - Thais B. Zanata; Bo Dalsgaard; Fernando C. Passos; Peter A. Cotton; James J. Roper; Pietro K. Maruyama; Erich Fischer; Matthias Schleuning; Ana M. Martín González; Jeferson Vizentin‐Bugoni; Donald C. Franklin; Stefan Abrahamczyk; et al. (Journal of Biogeography, 2017)
Aim Among the world's three major nectar‐feeding bird taxa, hummingbirds are the most phenotypically specialized for nectarivory, followed by sunbirds, while the honeyeaters are the least phenotypically specialized taxa. We tested whether this phenotypic specialization gradient is also found in the interaction patterns with their floral resources. Location Americas, Africa, Asia and Oceania/Australia. Methods We compiled interaction networks between birds and floral resources for 79 hummingbird, nine sunbird and 33 honeyeater communities. Interaction specialization was quantified through connectance ( C ), complementary specialization ( H 2 ′), binary ( Q B ) and weighted modularity ( Q ), with both observed and null‐model corrected values. We compared interaction specialization among the three types of bird–flower communities, both independently and while controlling for potential confounding variables, such as plant species richness, asymmetry, latitude, insularity, topography, sampling methods and intensity. Results Hummingbird–flower networks were more specialized than honeyeater–flower networks. Specifically, hummingbird–flower networks had a lower proportion of realized interactions (lower C ), decreased niche overlap (greater H 2 ′) and greater modularity (greater Q B ). However, we found no significant differences between hummingbird– and sunbird–flower networks, nor between sunbird– and honeyeater–flower networks. Main conclusions As expected, hummingbirds and their floral resources have greater interaction specialization than honeyeaters, possibly because of greater phenotypic specialization and greater floral resource richness in the New World. Interaction specialization in sunbird–flower communities was similar to both hummingbird–flower and honeyeater–flower communities. This may either be due to the relatively small number of sunbird–flower networks available, or because sunbird–flower communities share features of both hummingbird–flower communities (specialized floral shapes) and honeyeater–flower communities (fewer floral resources). These results suggest a link between interaction specialization and both phenotypic specialization and floral resource richness within bird–flower communities at a global scale.

Bacteria and fungi inactivation by photocatalysis under UVA irradiation: liquid and gas phase - Caio Rodrigues-Silva; Sandra M. Miranda; Filipe V. S. Lopes; Mário Silva; Márcia Dezotti; Adrián M. T. Silva; Joaquim L. Faria; Rui A. R. Boaventura; Vítor J. P. Vilar; Eugénia Pinto (Environmental Science and Pollution Research, 2017)

Whole genome sequencing of Guzerá cattle reveals genetic variants in candidate genes for production, disease resistance, and heat tolerance - Izinara C. Rosse; Juliana G. Assis; Francislon S. Oliveira; Laura R. Leite; Flávio Araujo; Adhemar Zerlotini; Angela Volpini; Anderson J. Dominitini; Beatriz C. Lopes; Wagner A. Arbex; Marco A. Machado; Maria G. C. D. Peixoto; et al. (Mammalian Genome, 2017)

Performance of Lynch syndrome predictive models in quantifying the likelihood of germline mutations in patients with abnormal MLH1 immunoexpression - Verónica Cabreira; Carla Pinto; Manuela Pinheiro; Paula Lopes; Ana Peixoto; Catarina Santos; Isabel Veiga; Patrícia Rocha; Pedro Pinto; Rui Henrique; Manuel R. Teixeira (Familial Cancer, 2017)

Erratum to: Habitat selection disruption and lateralization impairment of cryptic flatfish in a warmer, hypercapnic, and contaminated ocean - Eduardo Sampaio; Ana Luísa Maulvault; Vanessa M. Lopes; José R. Paula; Vera Barbosa; Ricardo Alves; Pedro Pousão-Ferreira; Tiago Repolho; António Marques; Rui Rosa (Marine Biology, 2016)

Impact of air exposure on the photobiology and biochemical profile of an aggressive intertidal competitor, the zoanthid Palythoa caribaeorum - Inês C. Rosa; Rui J. M. Rocha; Ana Lopes; Igor C. S. Cruz; Ricardo Calado; Narcisa Bandarra; Ruy K. Kikuchi; Amadeu M. V. M. Soares; João Serôdio; Rui Rosa (Marine Biology, 2016)

Habitat selection disruption and lateralization impairment of cryptic flatfish in a warm, acid, and contaminated ocean - Eduardo Sampaio; Ana Luísa Maulvault; Vanessa M. Lopes; José R. Paula; Vera Barbosa; Ricardo Alves; Pedro Pousão-Ferreira; Tiago Repolho; António Marques; Rui Rosa (Marine Biology, 2016)

Comparative study on metal biosorption by two macroalgae in saline waters: single and ternary systems - Paula Figueira; Bruno Henriques; Ana Teixeira; Cláudia B. Lopes; Ana T. Reis; Rui J. R. Monteiro; A. C. Duarte; M. A. Pardal; E. Pereira (Environmental Science and Pollution Research, 2016)

Axonal elongation and dendritic branching is enhanced by adenosine A2A receptors activation in cerebral cortical neurons - Filipa F. Ribeiro; Raquel Neves-Tomé; Natália Assaife-Lopes; Telma E. Santos; Rui F. M. Silva; Dora Brites; Joaquim A. Ribeiro; Mónica M. Sousa; Ana M. Sebastião (Brain Structure and Function, 2016)

Neuro-oxidative damage and aerobic potential loss of sharks under elevated CO2 and warming - Rui Rosa; José Ricardo Paula; Eduardo Sampaio; Marta Pimentel; Ana R. Lopes; Miguel Baptista; Miguel Guerreiro; Catarina Santos; Derek Campos; Vera M.F. Almeida-Val; Ricardo Calado; Mário Diniz; et al. (Marine Biology, 2016)

Deficit in digestive capabilities of bamboo shark early stages under climate change - Rui Rosa; Marta Pimentel; Juan G. Galan; Miguel Baptista; Vanessa M. Lopes; Ana Couto; Miguel Guerreiro; Eduardo Sampaio; Joana Castro; Catarina Santos; Ricardo Calado; Tiago Repolho (Marine Biology, 2016)

Exercise Improves Cognitive Impairment and Dopamine Metabolism in MPTP-Treated Mice - Aderbal S. Aguiar; Samantha C. Lopes; Fabrine S. M. Tristão; Daniel Rial; Gisele de Oliveira; Cláudio da Cunha; Rita Raisman-Vozari; Rui D. Prediger (Neurotoxicity Research, 2016)

Impairment of habitat selection judgement and lateralization on a cryptic flatfish under future contaminated ocean conditions - Sampaio Eduardo; Maulvault Ana; Lopes Vanessa; Paula Jose; Barbosa Vera; Alves Ricardo; Pousao-Ferreira Pedro; Repolho Tiago; Marques Antonio; Rosa Rui (Frontiers in Marine Science, 2016)

Effect of different diets on growth of the ciliate protozoan Euplotes sp. - Mendes Catarina; Chambel João; Lopes João; Calado Rui; Maranhão Paulo (Frontiers in Marine Science, 2016)

Unraveling the interactive effects of climate change and oil contamination on laboratory‐simulated estuarine benthic communities - Francisco J. R. C. Coelho; Daniel F. R. Cleary; Rui J. M. Rocha; Ricardo Calado; José M. Castanheira; Sílvia M. Rocha; Artur M. S. Silva; Mário M. Q. Simões; Vanessa Oliveira; Ana I. Lillebø; Adelaide Almeida; Ângela Cunha; et al. (Global Change Biology, 2015)
There is growing concern that modifications to the global environment such as ocean acidification and increased ultraviolet radiation may interact with anthropogenic pollutants to adversely affect the future marine environment. Despite this, little is known about the nature of the potential risks posed by such interactions. Here, we performed a multifactorial microcosm experiment to assess the impact of ocean acidification, ultraviolet B (UV‐B) radiation and oil hydrocarbon contamination on sediment chemistry, the microbial community (composition and function) and biochemical marker response of selected indicator species. We found that increased ocean acidification and oil contamination in the absence of UV‐B will significantly alter bacterial composition by, among other things, greatly reducing the relative abundance of Desulfobacterales , known to be important oil hydrocarbon degraders. Along with changes in bacterial composition, we identified concomitant shifts in the composition of oil hydrocarbons in the sediment and an increase in oxidative stress effects on our indicator species. Interestingly, our study identifies UV‐B as a critical component in the interaction between these factors, as its presence alleviates harmful effects caused by the combination of reduced pH and oil pollution. The model system used here shows that the interactive effect of reduced pH and oil contamination can adversely affect the structure and functioning of sediment benthic communities, with the potential to exacerbate the toxicity of oil hydrocarbons in marine ecosystems.

Superoxide Dismutase Enzymosomes: Carrier Capacity Optimization, in Vivo Behaviour and Therapeutic Activity - M. Luísa Corvo; H. Susana Marinho; Paulo Marcelino; Rui M. Lopes; Carlos A. Vale; Claúdia R. Marques; Luísa C.D. Martins; Peter Laverman; Gert Storm; M. Bárbara A.F. Martins (Pharmaceutical Research, 2015)

Solar photocatalytic gas-phase degradation of n-decane—a comparative study using cellulose acetate monoliths coated with P25 or sol-gel TiO2 films - Sandra M. Miranda; Filipe V. S. Lopes; Caio Rodrigues-Silva; Susana D. S. Martins; Adrián M. T. Silva; Joaquim L. Faria; Rui A. R. Boaventura; Vítor J. P. Vilar (Environmental Science and Pollution Research, 2015)

Synthesis and characterization of N-modified titania nanotubes for photocatalytic applications - Ricardo A. R. Monteiro; Filipe V. S. Lopes; Rui A. R. Boaventura; Adrián M. T. Silva; Vítor J. P. Vilar (Environmental Science and Pollution Research, 2015)

Evaluation and Selection of Indicators for Land Degradation and Desertification Monitoring: Types of Degradation, Causes, and Implications for Management - Or. Kairis; C. Kosmas; Ch. Karavitis; C. Ritsema; L. Salvati; S. Acikalin; M. Alcalá; P. Alfama; J. Atlhopheng; J. Barrera; A. Belgacem; A. Solé-Benet; et al. (Environmental Management, 2014)

Evaluation and Selection of Indicators for Land Degradation and Desertification Monitoring: Methodological Approach - C. Kosmas; Or. Kairis; Ch. Karavitis; C. Ritsema; L. Salvati; S. Acikalin; M. Alcalá; P. Alfama; J. Atlhopheng; J. Barrera; A. Belgacem; A. Solé-Benet; et al. (Environmental Management, 2014)

V S profile: measured versus empirical correlations—a Lower Tagus river valley example - Isabel Lopes; Jaime A. Santos; Rui Carrilho Gomes (Bulletin of Engineering Geology and the Environment, 2014)

Ocean cleaning stations under a changing climate: biological responses of tropical and temperate fish‐cleaner shrimp to global warming - Rui Rosa; Ana Rita Lopes; Marta Pimentel; Filipa Faleiro; Miguel Baptista; Katja Trübenbach; Luis Narciso; Gisela Dionísio; Maria Rita Pegado; Tiago Repolho; Ricardo Calado; Mário Diniz (Global Change Biology, 2014)
Cleaning symbioses play an important role in the health of certain coastal marine communities. These interspecific associations often occur at specific sites (cleaning stations) where a cleaner organism (commonly a fish or shrimp) removes ectoparasites/damaged tissue from a ‘client’ (a larger cooperating fish). At present, the potential impact of climate change on the fitness of cleaner organisms remains unknown. This study investigated the physiological and biochemical responses of tropical ( Lysmata amboinensis ) and temperate ( L. seticaudata ) cleaner shrimp to global warming. Specifically, thermal limits ( CTM ax), metabolic rates, thermal sensitivity, heat shock response ( HSR ), lipid peroxidation [malondialdehyde ( MDA ) concentration], lactate levels, antioxidant ( GST , SOD and catalase) and digestive enzyme activities (trypsin and alkaline phosphatase) at current and warming (+3 °C) temperature conditions. In contrast to the temperate species, CTM ax values decreased significantly from current (24–27 °C) to warming temperature conditions (30 °C) for the tropical shrimp, where metabolic thermal sensitivity was affected and the HSR was significantly reduced. MDA levels in tropical shrimp increased dramatically, indicating extreme cellular lipid peroxidation, which was not observed in the temperate shrimp. Lactate levels, GST and SOD activities were significantly enhanced within the muscle tissue of the tropical species. Digestive enzyme activities in the hepatopancreas of both species were significantly decreased by warmer temperatures. Our data suggest that the tropical cleaner shrimp will be more vulnerable to global warming than the temperate Lysmata seticaudata ; the latter evolved in a relatively unstable environment with seasonal thermal variations that may have conferred greater adaptive plasticity. Thus, tropical cleaning symbioses may be challenged at a greater degree by warming‐related anthropogenic forcing, with potential cascading effects on the health and structuring of tropical coastal communities (e.g. coral reefs).

Developmental and physiological challenges of octopus (Octopus vulgaris) early life stages under ocean warming - Tiago Repolho; Miguel Baptista; Marta S. Pimentel; Gisela Dionísio; Katja Trübenbach; Vanessa M. Lopes; Ana Rita Lopes; Ricardo Calado; Mário Diniz; Rui Rosa (Journal of Comparative Physiology B, 2014)

Physiological and behavioral responses of temperate seahorses (Hippocampus guttulatus) to environmental warming - Maria Aurélio; Filipa Faleiro; Vanessa M. Lopes; Vanessa Pires; Ana Rita Lopes; Marta S. Pimentel; Tiago Repolho; Miguel Baptista; Luís Narciso; Rui Rosa (Marine Biology, 2013)

Development and validation of an experimental life support system for assessing the effects of global climate change and environmental contamination on estuarine and coastal marine benthic communities - Francisco J. R. C. Coelho; Rui J. M. Rocha; Ana C. C. Pires; Bruno Ladeiro; José M. Castanheira; Rodrigo Costa; Adelaide Almeida; Ângela Cunha; Ana Isabel Lillebø; Rui Ribeiro; Ruth Pereira; Isabel Lopes; et al. (Global Change Biology, 2013)
An experimental life support system ( ELSS ) was constructed to study the interactive effects of multiple stressors on coastal and estuarine benthic communities, specifically perturbations driven by global climate change and anthropogenic environmental contamination. The ELSS allows researchers to control salinity, pH , temperature, ultraviolet radiation ( UVR ), tidal rhythms and exposure to selected contaminants. Unlike most microcosms previously described, our system enables true independent replication (including randomization). In addition to this, it can be assembled using commercially available materials and equipment, thereby facilitating the replication of identical experimental setups in different geographical locations. Here, we validate the reproducibility and environmental quality of the system by comparing chemical and biological parameters recorded in our ELSS with those prevalent in the natural environment. Water, sediment microbial community and ragworm (the polychaete Hediste diversicolor ) samples were obtained from four microcosms after 57 days of operation. In general, average concentrations of dissolved inorganic nutrients ( NO 3 − ; NH 4 + and PO 4 −3 ) in the water column of the ELSS experimental control units were within the range of concentrations recorded in the natural environment. While some shifts in bacterial community composition were observed between in situ and ELSS sediment samples, the relative abundance of most metabolically active bacterial taxa appeared to be stable. In addition, ELSS operation did not significantly affect survival, oxidative stress and neurological biomarkers of the model organism Hediste diversicolor . The validation data indicate that this system can be used to assess independent or interactive effects of climate change and environmental contamination on benthic communities. Researchers will be able to simulate the effects of these stressors on processes driven by microbial communities, sediment and seawater chemistry and to evaluate potential consequences to sediment toxicity using model organisms such as Hediste diversicolor .

Contaminant driven genetic erosion and associated hypotheses on alleles loss, reduced population growth rate and increased susceptibility to future stressors: an essay - Rui Ribeiro; Isabel Lopes (Ecotoxicology, 2013)

Manganese-exposed developing rats display motor deficits and striatal oxidative stress that are reversed by Trolox - Fabiano M. Cordova; Aderbal S. Aguiar; Tanara V. Peres; Mark W. Lopes; Filipe M. Gonçalves; Daniela Z. Pedro; Samantha C. Lopes; Célso Pilati; Rui D. S. Prediger; Marcelo Farina; Keith M. Erikson; Michael Aschner; et al. (Archives of Toxicology, 2013)

Variable within-brood maternal provisioning in newly extruded embryos of Homarus gammarus - Miguel Costa Leal; Patricia N. Pochelon; Teresa Lopes da Silva; Alberto Reis; Rui Rosa; Ricardo Calado (Marine Biology, 2013)

Assessment of indoor airborne contamination in a wastewater treatment plant - Juliana V. Teixeira; Sandra Miranda; Ricardo A. R. Monteiro; Filipe V. S. Lopes; Joana Madureira; Gabriela V. Silva; Nazaré Pestana; Eugénia Pinto; Vítor J. P. Vilar; Rui A. R. Boaventura (Environmental Monitoring and Assessment, 2013)

Reproduction in Octocorallia: Synchronous spawning and asynchronous oogenesis in the pennatulid Veretillum cynomorium - Vanessa M. Lopes; Miguel Baptista; Marta S. Pimentel; Tiago Repolho; Luis Narciso; Rui Rosa (Marine Biology Research, 2012)

Evaluating the possible anticoagulant and antioxidant effects of sulfated polysaccharides from the tropical green alga Caulerpa cupressoides var. flabellata - Mariana Santana Santos Pereira Costa; Leandro Silva Costa; Sara Lima Cordeiro; Jailma Almeida-Lima; Nednaldo Dantas-Santos; Kaline Dantas Magalhães; Diego Araujo Sabry; Ivan Rui Lopes Albuquerque; Marcia Rodrigues Pereira; Edda Lisboa Leite; Hugo Alexandre Oliveira Rocha (Journal of Applied Phycology, 2012)

A multi-biomarker approach in cross-transplanted mussels Mytilus galloprovincialis - Angela Serafim; Belisandra Lopes; Rui Company; Alexandra Cravo; Tânia Gomes; Vânia Sousa; Maria João Bebianno (Ecotoxicology, 2011)

Erratum to: Cleanup of atrazine-contaminated soils: ecotoxicological study on the efficacy of a bioremediation tool with Pseudomonas sp. ADP - Sónia Chelinho; Matilde Moreira-Santos; Débora Lima; Cátia Silva; Paula Viana; Sandra André; Isabel Lopes; Rui Ribeiro; Arsénio M. Fialho; Cristina A. Viegas; José P. Sousa (Journal of Soils and Sediments, 2010)

A Preformulation Study of a New Medicine for Chagas Disease Treatment: Physicochemical Characterization, Thermal Stability, and Compatibility of Benznidazole - José Lamartine Soares-Sobrinho; Mônica Felts de La Roca Soares; Pablo Queiroz Lopes; Lidiane Pinto Correia; Fábio Santos de Souza; Rui Oliveira Macêdo; Pedro José Rolim-Neto (AAPS PharmSciTech, 2010)

Kalirin: a novel genetic risk factor for ischemic stroke - Tiago Krug; Helena Manso; Liliana Gouveia; João Sobral; Joana M. Xavier; Isabel Albergaria; Gisela Gaspar; Manuel Correia; Miguel Viana-Baptista; Rita Moiron Simões; Amélia Nogueira Pinto; Ricardo Taipa; et al. (Human Genetics, 2010)

Cleanup of atrazine-contaminated soils: ecotoxicological study on the efficacy of a bioremediation tool with Pseudomonas sp. ADP - Sónia Chelinho; Matilde Moreira-Santos; Débora Lima; Cátia Silva; Paula Viana; Sandra André; Isabel Lopes; Rui Ribeiro; Arsénio M. Fialho; Cristina A. Viegas; José P. Sousa (Journal of Soils and Sediments, 2010)

TP53 germline mutations in Portugal and genetic modifiers of age at cancer onset - Carla Pinto; Isabel Veiga; Manuela Pinheiro; Ana Peixoto; Armando Pinto; José M. Lopes; Rui M. Reis; Carla Oliveira; Manuela Baptista; Lúcia Roque; Fernando Regateiro; Luís Cirnes; et al. (Familial Cancer, 2009)

Multiplicity of aspartic proteinases from Cynara cardunculus L. - Ana Cristina Sarmento; Henrique Lopes; Cláudia S. Oliveira; Rui Vitorino; Bart Samyn; Kjell Sergeant; Griet Debyser; Jozef Van Beeumen; Pedro Domingues; Francisco Amado; Euclides Pires; M. Rosário M. Domingues; et al. (Planta, 2009)

Relevant principal component analysis applied to the characterisation of Portuguese heather honey - Rui C. Martins; Victor V. Lopes; Patrícia Valentão; João C.M.F. Carvalho; Paulo Isabel; Maria T. Amaral; Maria T. Batista; Paula B. Andrade; Branca M. Silva (Natural Product Research, 2008)

Hypermethylation of Cyclin D2 is associated with loss of mRNA expression and tumor development in prostate cancer - Rui Henrique; Vera Lúcia Costa; Nuno Cerveira; André Lopes Carvalho; Mohammad Obaidul Hoque; Franclim Ricardo Ribeiro; Jorge Oliveira; Manuel Rodrigues Teixeira; David Sidransky; Carmen Jerónimo (Journal of Molecular Medicine, 2006)

Cervical cancer and CYP2E1 polymorphisms: implications for molecular epidemiology - Paula M. Ferreira; Raquel Catarino; Deolinda Pereira; Ana Matos; Daniela Pinto; Ana Coelho; Carlos Lopes; Rui Medeiros (European Journal of Clinical Pharmacology, 2006)

Glutathione S-Transferase Genotype GSTM1 as a Predictor of Elevated Angiogenic Phenotype in Patients with Early Onset Breast Cancer - Rui Medeiros; Raquel Soares; André Vasconcelos; Fernando Schmitt; Carlos Lopes (Angiogenesis, 2004)

Overexpression of the cat-86 Gene Is Associated with Thermosensitivity in Bacillus subtilis - S. Marvin Friedman; Saikrishna Chatakondu; Diane Urbanski; Rui Lopes (Current Microbiology, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)